2006
DOI: 10.1002/anie.200503738
|View full text |Cite
|
Sign up to set email alerts
|

Organic–Inorganic Sn12 and Organic Sn6 Oxide–Hydroxide Clusters

Abstract: Organic meets inorganic: Hydrolysis of an aryl trialkynyl tin compound leads to an organic–inorganic tin oxide–hydroxide cluster, which consists of an inorganic tin oxide core surrounded by eight aryl tin fragments (see picture, left; Sn green, inorganic Sn blue, O red, C gray, H pink). Slightly modified reaction conditions produce a hexameric aryl tin oxide–hydroxide cage, which can be described as a double‐twist Möbius band (see picture, right).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 19 publications
1
32
0
1
Order By: Relevance
“…27 Gradient-selected 1 H-119 Sn HMQC (heteronuclear multiplequantum correlation) spectra 28,29 were recorded with evolution delays for the n J( 1 H-119 Sn) couplings set to 10,33,and 125 ms (50,15,and 4 Hz). 1 H-13 C and 1 H-119 Sn HSQC (heteronuclear single-quantum correlation) spectra were recorded with adiabatic 180°pulses in phase-sensitive and gradient-selected modes with GARP4 decoupling.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Gradient-selected 1 H-119 Sn HMQC (heteronuclear multiplequantum correlation) spectra 28,29 were recorded with evolution delays for the n J( 1 H-119 Sn) couplings set to 10,33,and 125 ms (50,15,and 4 Hz). 1 H-13 C and 1 H-119 Sn HSQC (heteronuclear single-quantum correlation) spectra were recorded with adiabatic 180°pulses in phase-sensitive and gradient-selected modes with GARP4 decoupling.…”
Section: Methodsmentioning
confidence: 99%
“…So far, only three such species were reported: Sn 3 O(O i Bu) 10 (HO i Bu) 2 , 11 Sn 4 O 2 (OEt) 10 (acac) 2 , 12 and [SnO(O t Bu)(OAc)] 6 . 13 This trio constitutes quite a small group, especially when compared to the large family formed by titanium oxo clusters.…”
Section: Introductionmentioning
confidence: 97%
“…58 (RSn) 8 (O) 14 (OH) 8 (SnOH) 4 (R = 2,4,6-i Pr 3 C 6 H 2 ). 59 These structural studies offer insights into the evolution of the final oxide material in a way that is impossible for gas-phase CVD chemistry.…”
Section: Sol-gel Precursorsmentioning
confidence: 99%
“…1,3-Dihydro-1,3-dioxa-2,4-distannetanes are usually prepared in two different ways, either by hydrolysis of tin halides or by condensation between a tin oxide or hydroxide and an acid, often under Dean-Stark conditions. During the course of our studies concerning the hydrolysis of organotrialkynyltins [21][22][23][24][25] and bridged organohexaalkynylditins [26][27][28][29] we showed that the use of a bulky substituent on the tin, such as the 2,4,6-trii-propylphenyl group, could allow the isolation of clusters of monoorganotin oxides-hydroxides of various sizes and shapes. When hydrolysis was conducted in the presence of an aromatic sulfonic acid, cationic polysulfonates with three or ten tin atoms and two types of sulfonate bondings, an electrostatic and a bridging one, were isolated [22].…”
Section: Introductionmentioning
confidence: 99%